itu Efektivitas Pembelajaran IPA Berbasis Proyek Melalui Pembuatan Poster Terhadap Kesadaran Mitigasi Bencana Gempa Bumi - Khansa Nur Shafa Felisyah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2025)
This study aimed to investigate the effectiveness of a project-based learning (PjBL) model in science education through poster creation to enhance students’ awareness of earthquake disaster mitigation in Year 8 at SMP Negeri 3 Gresik. The research employed a quasi-experimental design using a pre-test–post-test control group. The participants consisted of two classes: the experimental group, which was taught using the PjBL model through poster projects, and the control group, which received conventional instruction. The research instrument was a disaster mitigation awareness questionnaire that had been validated beforehand. The findings revealed that the mean score of students’ awareness in the experimental group was higher than that of the control group, with the experimental group categorised as “very good” (88.4%) and the control group as “good” (76.5%). An independent samples t-test yielded a significance value of p = 0.014 < 0.05, indicating a significant difference between the two groups. These results suggested that project-based science learning through poster creation was effective in improving students’ awareness of earthquake disaster mitigation at the lower secondary level.